HIV-Associated benign lymphoepithelial parotid cysts: a rare case report - Sigdel, Brihaspati; Acharya, Priti; Maharjan, Rajesh; Sah, Kusheswar (Journal of Gandaki Medical College-Nepal, 2021)
Approximately one to 10% of patients with Human Immunodeficiency virus (HIV) infection associated with salivary gland disease. The presence of Benign lymphoepithelial cyst (BLEC) in the parotid gland is an indicator of HIV Infection. The diagnosis is usually based on a clinical course and HIV confirmatory blood testing. We have reported a case of a 35 years old Nepalese male patient with swelling of the bilateral parotid glands and HIV associated BLEC confirmed by Rapid diagnostic test kit (Determine unigold stat pack).